Utilization of Social Media Platforms to Increase Visibility and Sales of MSMEs in Pondok Legi Pepelegi, Sidoarjo - Karya, Denis Fidita; Mardhotillah, Rachma Rizqina; Anshori, Mohamad Yusak (UKInstitute, 2026)
This community service aims to increase the visibility and sales of Micro, Small and Medium Enterprises (MSMEs) through the use of social media platforms such as Facebook and Instagram. This program was carried out at the Pondok Legi Pepelegi , Sidoarjo, with the participation of 40 MSME actors. This community service activity consists of socialization, training, and interactive discussions. The results of the evaluation showed a significant increase in participants' understanding of social media for marketing. Before the training, only 40% of the participants had a basic understanding of the use of social media, while after the training this figure increased to 90%. In conclusion, this activity succeeded in improving participants' skills in utilizing social media to increase visibility and expand the market. Further assistance programs are needed to maintain the sustainability of the positive impacts produced.